Prenatal diagnosis and molecular cytogenetic characterization of de novo partial trisomy 12q (12q24.21→qter) and partial monosomy 6q (6q27→qter) associated with coarctation of the aorta, ventriculomegaly and thickened nuchal fold - Chen, Chih-Ping; Chen, Yi-Yung; Chern, Schu-Rern; Wu, Peih-Shan; Su, Jun-Wei; Chen, Yu-Ting; Chen, Li-Feng; Wang, Wayseen (Gene, 2013)
We present rapid aneuploidy diagnosis of de novo partial trisomy 12q (12q24.21→qter) and partial monosomy 6q (6q27→qter) by aCGH using uncultured amniocytes in a fetus with coarctation of the aorta, ventriculomegaly and thickened nuchal fold. We discuss the association of TBX3, TBX5 and MED13L gene duplication with coarctation of the aorta, and the association of RNASET2 gene haploinsufficiency with ventriculomegaly in this case. ► We present concomitant del(6)(q27→qter) and dup(12)(q24.21→qter). ► The phenotype includes aortic coarctation and ventriculomegaly. ► We discuss the genotype–phenotype correlation.